New species and records of Orchidaceae from Costa Rica - Bogarín, Diego (Universidad de Costa Rica, 2008)
We present and illustrate 11 new records of Orchidaceae from Costa Rica, and propose a new combination in Acianthera for Pleurothallis aberrans. Barbosella orbicularis and Myoxanthus speciosus, previously recorded from Costa Rica on the basis of doubtful vouchers, are confirmed to occur in the country and illustrated from Costa Rican vouchers. Warmingia margaritacea is reduced to the synonymy of Warmingia zamorana, a species previously known only from Ecuador. A new species, Epidendrum zunigae is described. This species is similar to E. guanacastense and E. isomerum, from which it differs by the narrow, lanceolate leaves, the greenish flowers, the apical half of the column purple with the clinandrium white, the sepals 11 mm long, and the creamy yellow, cordiform, acute, bicallose lip, wich is somewhat convex in natural position.